Pengaruh Fasilitas Kantor dan Disiplin Kerja terhadap Kinerja Perangkat Desa Kalirahayu di Kecamatan Losari Kabupaten Cirebon - Ayip Febriansyah; Nur Afridah; Dumadi Dumadi; Slamet Bambang Riono; M Badrun Zaman (Lembaga Pengembangan Kinerja Dosen, 2026)
The level of public satisfaction with public services in Kalirahayu Village, Losari District, Cirebon Regency is still relatively low. This phenomenon is allegedly influenced by the quality of office facilities and the level of work discipline of village officials. This study aims to analyze the influence of office facilities and work discipline on the performance of village apparatus, both partially and simultaneously. The optimal performance of village apparatus is the key in realizing responsive, efficient, and community-satisfied public services. This study uses a quantitative approach with a survey method. The data collection technique was carried out through direct observation, structured interviews, and the distribution of questionnaires to 45 respondents consisting of village officials and service user communities. The research instrument is tested for validity and reliability before use. Data analysis was carried out with the help of SPSS software through multiple linear regression tests, t-tests, and F-tests to test the influence of each variable. The results of the study show that office facilities and work discipline have a positive and significant effect on the performance of village apparatus. Partially, both variables contribute to performance improvement, and simultaneously strengthen the effectiveness of public services. These findings affirm the importance of improving work facilities and establishing a disciplined work culture as the main strategy in improving the quality of public services at the village level. The practical implications of this research encourage the village government to evaluate and continuously improve work facilities and strengthen the work ethic of village officials.